Age-related differences to neck muscle activation latency as a potential risk factor to fall-related traumatic brain injuries. (April 2020) - Wood, Tyler A.; Hernandez, Manuel E.; Sosnoff, Jacob J.
Abstract: This investigation examined age-related differences in neck muscle activation latency in response to anterior and posterior postural perturbations to understand the potential implications in fall-related traumatic brain injuries. 57 adults were recruited and categorized into 3 groups based on age: Young (18–30 years old), Young-Old (60–74 years) and Old-Old (75–89 years) group. Study participants underwent six anterior and posterior postural perturbations while bilateral sternocleidomastoid, upper trapezius, and splenius capitis electromyography was collected. Muscle activation latency time was calculated with established procedures. During anterior translations, a significant group effect for muscle activation latency of the right SCM ( F (2, 43) = 8.786, p  < 0.001), right ( F (2, 34) = 4.838, p  = 0.014) and left ( F (2, 34) = 5.015, p  = 0.012) upper trapezius, and right ( F (2, 45) = 3.195, p  = 0.050) and left ( F (2, 45) = 3.819, p  = 0.029) splenius capitis was observed. During posterior translations, a significant group effect for muscle activation latency was observed in the right ( F (2, 34) = 6.419, p  = 0.004) and left ( F (2, 41) = 5.275, p  = 0.009) SCM, and the right ( F (2, 34) = 4.925, p  = 0.013) and left ( F (2, 32) = 4.055, p  = 0.027) upper trapezius. Both older groups displayed longer muscle activation latencies than the young group. The age-related differences in neck muscle activation latency may be placing older adults at a greater risk of fall-related traumatic brain injuries.